Impact of Cochlear Trauma Degree and Localization on Intracochlear Electrocochleographic Recordings - David Bächinger; Merlin Schär; Ahmet Kunut; Rahel Bertschinger; Ivo Dobrev; Leanne Sijgers; Andreas H. Eckhard; Adrian Dalbert (Audiology Research)
Background/Objectives: Electrocochleography (ECochG) is a promising tool to monitor preservation of cochlear structures and function during cochlear implant (CI) surgery. However, the interpretation of ECochG signal changes during insertion of the CI electrode array remains controversial. This study investigates the influence of the degree and localization of cochlear trauma on ECochG signal changes using a mouse model. Methods: C57BL/6J-Crl1 mice underwent intracochlear ECochG recordings during the insertion of a platinum–iridium electrode. Results: In case of grade 1 and 2 cochlear trauma, as determined by post-mortem histological analysis, we found that a reduction in intracochlear cochlear microphonic (CM) amplitude correlates more significantly with the location of the trauma than with its severity. The more basally a trauma is located, the larger the CM amplitude drop. Furthermore, the results revealed that grade 1 or 2 trauma was detectable through ECochG before more severe trauma developed. Conclusions: These findings suggest that intracochlear ECochG can serve as a reliable intraoperative tool for detecting early and possibly reversible cochlear trauma, preventing more severe damage and aiding hearing preservation. The results emphasize the need for a nuanced interpretation of CM signal drops, considering trauma location and cochlear structure integrity at the site of trauma and apical to it.